FAMILY ANISOPODIDAE - Amorim, Dalton De Souza; Falaschi, Rafaela Lopes; Oliveira, Sarah Siqueira (Zootaxa, 2016)
This considerably small family is poorly known in Colombia, with only two species reported for the genus Sylvicola Harris (1776) so far. We synonymize Neomesochria Amorim & Tozoni (1994) to Mycetobia Meigen (1818), hence transferring the Dominican amber species Neomesochria antillea (Grimaldi 1991) and N. cryptambra (Grimaldi 1991), and the recent Neotropical species N. limanda (Stone 1966) and N. stonei (Lane & d’Andretta 1958) back to the genus Mycetobia. This paper provides new records for Mycetobia and Olbiogaster Osten-Sacken (1886) for Colombia.